Stappia aggregata Gl DAN Alteromonas sp.G2 BAKTERIPENDEGRADASI PHENANTRENE YANG DIISOLASIDARI LINGKUNGAN LAUT - Dyah Supriyati (BERITA BIOLOGI, 2009)
Stappia aggregata Gl and Alteromonas sp. G2 are marine bacteria isolated from Kepulauan Seribu waters, Jakarta. These bacteria were isolated using ONR7a media, and forming clear zone surrounding grown colonies after 48 hours, and able to grow on phenantrene as the sole carbon sources. After 4 hours incubation phnenantrene was degraded, and almost 12 hours about 60% of phenantrene was converted. The two strains performed similar biodegradation pattern, but different in growth characteristic.Bacteria Stappia aggregata Gl and Alteromonas sp. G2 grew optimum at 30°C, pH 8 and 3% salinity.